Ambient Light Monitoring and Control Using Internet of Things - Felix, Titosse Moises (2018)
Having good lighting in an environment is not only a matter of having smart lights which turns on and off automatically due to user occupancy. The lighting must be uniformly distributed and with the correct amount of brightness or intensity displayed to the user. Ambient light monitoring and control with IOT has been enabled to the highest level with the use of Zigbee technology. Currently, ambient light monitoring and control is divided by two: The first one has to do with turning ON/OFF at certain times of a day or based on the human presence, which is mainly focused on energy saving. The second which is still the objective of this project, is a concept of distributed light to the users. The objective of this project is to design a smart system for ambient light monitoring and control using Internet of Things (IoT) for distributed illumination with multiple lights.